2005
DOI: 10.1021/np049592f
|View full text |Cite
|
Sign up to set email alerts
|

Communiols E−H:  New Polyketide Metabolites from the Coprophilous Fungus Podospora communis

Abstract: Communiols E-H (1-4), four new polyketide-derived natural products containing furanocyclopentane, furanocyclopentene, cyclopentene, or γ-lactone moieties, have been isolated from two geographically distinct isolates of the coprophilous fungus Podospora communis. The structures of these compounds were determined by analysis of NMR and MS data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…HMBC data confirmed that the remainder of the structure of 7.8 matched that of 7.7, with the stereochemical assignment presumed to be analogous to that of 7.7. these compounds. [196][197][198][199][200][201][202][203] Communiols I -O (7.3 -7.9) contain the same skeleton and share similar presumed polyketide biogenetic origins with the other known communiols. Interestingly, this relatively simple, highly reduced group of eleven-carbon compounds has few particularly close analogues and is thus far known only from Podospora spp.…”
Section: Podospora Appendiculatamentioning
confidence: 99%
See 4 more Smart Citations
“…HMBC data confirmed that the remainder of the structure of 7.8 matched that of 7.7, with the stereochemical assignment presumed to be analogous to that of 7.7. these compounds. [196][197][198][199][200][201][202][203] Communiols I -O (7.3 -7.9) contain the same skeleton and share similar presumed polyketide biogenetic origins with the other known communiols. Interestingly, this relatively simple, highly reduced group of eleven-carbon compounds has few particularly close analogues and is thus far known only from Podospora spp.…”
Section: Podospora Appendiculatamentioning
confidence: 99%
“…Our preliminary investigations of coprophilous fungi have afforded a variety of new secondary metabolites, many of which show antibacterial or antifungal properties. [193][194][195][196][197] The genus Podospora has been of interest in our research due to the limited number of chemical studies of this taxonomic group that have been reported, despite its widespread occurrence and literature describing more than 80 named species. 94 Preliminary results obtained in our earlier work on a few selected members of this genus have been particularly fruitful, suggesting that more studies of these fungi as sources of new bioactive natural products would be worthwhile.…”
Section: Podospora Appendiculatamentioning
confidence: 99%
See 3 more Smart Citations